Pengalaman Peserta Didik Kelas 1 SD Dalam Menggunakan Quizizz Sebagai Sarana Belajar Interaktif - Zaki Dhamayanti1, Miki; Hidayati, Dian; Hasanah, Enung; Sukirman, Sukirman (Manajemen Pendidikan, 2024)
This research aims to understand and explore the experiences of 1st grade elementary school students in using Quizizz as an interactive learning medium. Each student's learning experience can vary based on various factors such as individual preferences, learning methods, and their educational background. Therefore, the focus of this research is to understand more deeply how these students interact with Quizizz, starting from their level of motivation to their experience in practical use of this application as well as seeing how this tool influences their motivation, participation and academic achievement. This type of research is qualitative research with the research method used, namely descriptive. The data collection process is carried out through purposive sampling where the researcher decides to determine the individuals and locations to study and understand the central phenomenon. This research was conducted at SD Muhammadiyah Tonggalan Klaten, namely in class 1D with 1 teacher and 10 students. The data collection process was carried out using in-depth structured interviews with class 1D teachers. Next, for 10 students, a focus group discussion (FGD) was carried out which was divided into 2 sessions with each session consisting of 5 students. Using Quizizz as an interactive learning tool for 1st grade elementary school students provides a positive experience and has an impact on their learning motivation. Students enjoy the interactivity, variety of questions, and gaming elements offered by this platform. Positive impacts are also seen in increasing students' active participation, self-confidence and intrinsic motivation. From a teacher's perspective, Quizizz is considered effective in enhancing learning and providing a useful evaluation tool. Therefore, the integration of Quizizz in 1st grade elementary school learning can be considered a positive step to improve the quality of education through the effective use of technology.